(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
The paper gives an overview of the study of Raetic. Part one contains introductory remarks concerning the structure of the corpus, research history and editions, archaeology and ancient sources, chronology and distribution, types of inscriptions and supports, alphabets, onomastics and language. Part 2 discusses open questions and possible lines of future research.